Direct and maternal genetic effects for growth traits in indubrazil cattle. - Ríos Utrera, íngel; Hernández Hernández, Víctor Delio; Amezcua Manjarrez, Eugenio Villagómez; Zárate Martínez, Juan Prisciliano; Villagómez Cortés, José Alfredo (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The objective was to estimate (co)variance components and genetic parameters for birth weight, adjusted 205-day (d) weaning weight, and adjusted 365-d yearling weight of Mexican Indubrazil calves obtained from an experimental herd under tropical conditions. (Co)variance components and genetic parameters were estimated fitting single-trait animal models with the MTDFREML program. For birth weight, the model included the direct and maternal genetic effects as well as the (co)variance between these two effects. The model for adjusted 205-d weaning weight was similar to the one for birth weight, but also included the maternal permanent environmental effect. The animal model to analyze adjusted 365-d yearling weight included the direct genetic effect. For birth weight and adjusted 205-d weaning weight, direct genetic effects were more important than maternal genetic effects. Estimates of direct heritability were: 0.27, 0.11 and 0.13 for birth weight, adjusted 205-d weaning weight and adjusted 365-d yearling weight, respectively. Estimates of maternal heritability were: 0.10 and 0.09 for birth weight and adjusted 205-d weaning weight, respectively. The estimate of the correlation between direct and maternal effects for adjusted 205-d weaning weight was relatively low (-0.27). Estimates of direct heritability for weaning and yearling weights suggest that such traits could be increased by direct selection.